2000
DOI: 10.1093/jnci/92.13.1081
|View full text |Cite
|
Sign up to set email alerts
|

Breast Density as a Predictor of Mammographic Detection: Comparison of Interval- and Screen-Detected Cancers

Abstract: Mammographic breast density appears to be a major risk factor for interval cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
571
2
26

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 922 publications
(627 citation statements)
references
References 34 publications
28
571
2
26
Order By: Relevance
“…This was true independent of use of HRT. This result was in agreement with the study of Mandelson et al, 29 who found an odds ratio of 6.14 for interval cancer when comparing women with extremely dense breasts to women with extremely fat breasts. Use of HRT and its effect on breast density has been in focus recently.…”
Section: Breast Density and Use Of Hrtsupporting
confidence: 93%
“…This was true independent of use of HRT. This result was in agreement with the study of Mandelson et al, 29 who found an odds ratio of 6.14 for interval cancer when comparing women with extremely dense breasts to women with extremely fat breasts. Use of HRT and its effect on breast density has been in focus recently.…”
Section: Breast Density and Use Of Hrtsupporting
confidence: 93%
“…Screening mammography has been demonstrated to increase the early detection of invasive and pre-invasive breast cancer, even if it has a high false-negative rate in women with dense breast tissue and is not an accurate methodology for early accurate measurement of response or for prediction of therapeutic response (20). Similarly, ultrasonography and CT are not extremely accurate in predicting therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, um possível mecanismo relacionando estroma a agressividade tumoral por meio de fatores de crescimento aí produzidos também pode estar associado 7 .…”
Section: Discussionunclassified
“…Essa involução é progressiva, porém não uniforme, pois algumas mulheres mantêm um padrão mamográfi co denso, traduzindo-se em predomínio de tecido fi broglandular 5 . Essa densidade radiológica elevada assume importância, pois é considerada por alguns como um dos fatores de risco independentes para câncer de mama 1,[5][6][7][8] .…”
Section: (Figura 1)unclassified